Evaluation of Corneas from Donors With Septicemia for Use in Corneal Transplant. Issue 8 (August 2016) - Nagaraja, Harsha; Anandula, Venkataramana; Kugar, Thungappa; Shivanna, Yathish; Shetty, Rohit
Abstract : Purpose: To evaluate if donor corneas obtained from deaths occurring because of septicemia can be used for corneal transplantation. Study Design: Prospective study. Methods: Eleven septicemic donor corneas were used in the study and 10 donor corneas from deaths because of causes other than septicemia were used as controls. Blood culture reports of all patients who had donated eyes were collected, and the pathogenic organisms causing septicemia were noted. On obtaining the eyeballs, aqueous and vitreous samples were sent for polymerase chain reaction to analyze for eubacterial and panfungal genomes. Corneal and scleral tissues (3 × 3 mm) were sent for culture in brain heart infusion media. Growth from each of the samples was checked to ascertain if the same organism was isolated in all. Results: One corneal and 3 scleral culture reports in the sepsis group and 1 corneal and 1 scleral culture report in the control group showed positive growth. Normal conjunctival/eyelid commensal organisms were isolated from all culture-positive samples and did not correlate with the pathogenic organism causing the septicemia. Three aqueous and vitreous samples in the sepsis group and 4 samples of aqueous and vitreous in the control group that tested positive for eubacterial genome showed no corresponding growth in the culture report of cornea and sclera. Conclusions: Corneal tissues harvested from septicemic donors do not necessarily harbor the pathogenic organisms causing the septicemia, suggesting that such corneas may be suitable for transplantation.